PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Junifar, Nurdiansyah; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of emotional intelligence, spiritual intelligence, andlearning behavior to the comprehension level of accounting.This research isa quantitative which hasbeen carried out by using comparative casual method which emphasizeson testing theories through themeasurement of the research variables by using statistic procedure. The population is theundergraduate students of 2011, or the final-years of accounting students who have taken 120 ofsemester credit system, the sample selection method has been done by using simple random samplingand 218 students have been selected as samples. The data analysis technique has been done by usingmultiple linear regressions. Based on the result of analysis and hypothesis test it can be concluded asfollow: (1) the emotional intelligence has positive influence to the comprehension of accounting. Itmeans that when the implementation of emotional intelligence is getting better, the comprehension ofaccounting will improve; (2) The spiritual intelligence has positive influence to the comprehension ofaccounting. It means that whentheapplication of spiritual intelligence is getting better, thecomprehension of accountingwill be increased; (3) Learning behavior has positive influence to thecomprehension of accounting. It means that learning behavior which is in appropriate with theobjectives of education is required, in which the learning behavior in accordance with the objective ofeducation can be achieved effectively and efficient, therefore the academic achievement can beimproved.Keywords: Emotional Intelligence, Spiritual Intelligence, Learning Behaviorand Comprehensionof Accounting.